1991
DOI: 10.1111/j.1532-5415.1991.tb01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Institutionalized Elderly: Relation to Sleep Apnea

Abstract: Sleep apnea is characterized by transient hypoxemias which are thought to affect mental functioning. Accordingly, speculation and research have focussed on relationships between sleep apnea and dementia. We studied 235 nursing home (ie institutionalized) patients (152 women with a median age of 83.5; 83 men with a median age of 79.7) with portable sleep recording equipment. The Mattis Dementia Rating Scale and the Geriatric Depression Scale were given to each. Seventy percent of the patients had five or more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
130
1
4

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 201 publications
(136 citation statements)
references
References 26 publications
1
130
1
4
Order By: Relevance
“…Such findings are not surprising as associations between OSA and some cognitive impairment are well established in multiple studies including sleep disorders clinic patients, older adults, patients with Alzheimer disease, and nursing home patients. [71][72][73][74][75][76][77][78][79] We also found that OSA treatment improves nighttime sleep in PD. 80 OSA treatment is therefore clinically indicated, as it may also reduce NMS impairment and improve quality of life.…”
mentioning
confidence: 56%
“…Such findings are not surprising as associations between OSA and some cognitive impairment are well established in multiple studies including sleep disorders clinic patients, older adults, patients with Alzheimer disease, and nursing home patients. [71][72][73][74][75][76][77][78][79] We also found that OSA treatment improves nighttime sleep in PD. 80 OSA treatment is therefore clinically indicated, as it may also reduce NMS impairment and improve quality of life.…”
mentioning
confidence: 56%
“…Besides sleep disruption, clinical sleep disorders are strongly comorbid with mild cognitive impairment (MCI) and AD. Over 60% of persons with MCI and AD have one or more sleep disturbances (Ancoli‐Israel, Klauber, Butters, Parker, & Kripke, 1991; Guarnieri et al, 2012), with sleep apnea and insomnia being most common.…”
Section: Lifestyle Associations and Interventions For Aging And Admentioning
confidence: 99%
“…This degeneration may place the patient at an increased risk of developing SRBD. For example, Ancoli-Israel et al 62 found that those institutionalized elderly with severe dementia had more severe SRBD compared to those with mild-moderate or no dementia. Furthermore, those with more severe SRBD performed worse on the dementia rating scales, suggesting that more severe SRBD was associated with more severe dementia.…”
Section: Sleep-related Breathing Disordermentioning
confidence: 99%